The effect of high-fat style diet and ovariectomy on inflammation and baroreflex control of renal sympathetic nerve activity / Yamuna Sucedaram - Yamuna, Sucedaram (2021)
High fat diet-induced visceral obesity, renal inflammation and injury can lead to augmented renal sympathetic nerve activity (RSNA). The mechanism for the increase in RSNA appears to be due to the blunting of the arterial and cardiopulmonary baroreflexes resulting from an inflammatory response. This study aimed to investigate the effect of high fat style diet (HFSD) and loss of ovarian function on structural changes and inflammatory response in the kidney as well as in the liver; and on the low- and highpressure baroreflex control of RSNA. To that end, ovary-intact and ovariectomised (OVX) Sprague Dawley rats received a normal diet (ND) or a HFSD for 10 weeks. Mean blood pressure (MBP) and fasting blood glucose were measured every two weeks. Renal functional parameters were assessed via 24h metabolic data collection. At the end of week 10, ovary-intact and OVX rats fed the ND or HFSD were anaesthetised for measurement of RSNA. Acute bilateral renal denervation (DNX) was performed, and baroreflex gain curves were constructed from the baroreflex changes in RSNA to vasopressor and vasodepressor drugs. Cardiopulmonary baroreflex control of RSNA was assessed by acute saline volume expansion (VE). Kidneys and liver were harvested for histological, immunohistochemical and immunofluorescence studies. Noradrenaline content was determined in the kidney by immunohistochemistry and ELISA. Visceral adiposity was significantly greater in all HFSD rats compared to their ND counterparts but fasting blood glucose and MBP were increased in OVX-HFSD rats compared to HFSD rats. Renal dysfunction was observed in all HFSD rats compared to the ND groups. In the acute study, baroreflex gain curve sensitivity (A2) of RSNA was decreased in both the HFSD and OVX-HFSD groups compared to their control counterparts but was normalised following iv DNX. VE reduced RSNA in ND fed groups but did not alter RSNA in both HFSD and OVX-HFSD groups; however, following DNX, HFSD and OVX-HFSD exhibited reduction in RSNA. Renal noradrenaline content was similar in all HFSD-fed rats but was greatly reduced in the denervated groups. Histological studies on kidney showed focal interstitial mononuclear cell infiltration in HFSD rats with mesangial expansion being greater in the OVX-HFSD rats. All HFSD fed rats exhibited increased expressions of renal inflammatory markers, namely IL-6, TNF-α and MCP-1, and infiltrating M1 macrophages with some influence of ovarian hormonal status. Similarly, HFSD-fed rats showed increased expressions of the inflammatory markers and M1 macrophage infiltration in the liver; however, only IL-6 expression was magnified in the OVX-HFSD rats. HFSD-feeding also caused hepatocellular steatosis which was aggravated in OVX rats, and only OVX-HFSD rats revealed hepatocellular ballooning. Our data suggest that some of the structural changes and inflammatory response in the kidney and liver of HFSD-fed rats are exacerbated by ovariectomy. On the other hand, HFSD-induced impairment of baroreflex control of RSNA occurred similarly in HFSD and OVX-HFSD rats although MBP was increased only in the ovarian hormones deprived-group suggesting that ovarian hormones could have modulatory role on other mechanisms that regulate BP in female obesity. Keywords: High fat style diet, obesity, renal sympathetic nerve activity, inflammation.